Removal of a fish bone endangering the common carotid artery under general anesthesia with video laryngoscope: A case report - Yang Lu; Hua Zhang; Jurong Xia; Haibo Xu; Jinglei Wang; Jie He (Heliyon, 2023)
A fish bone penetrating the digestive tract is a common emergency, and its removal often requires endoscopy. We report herein a case in which a fish bone punctured the throat; its front end was close to the common carotid artery, but its back end could not be visualized. Subsequently, we compared the pharyngeal CT and carotid CTA of the patient and found that the fishbone had shifted. So we considered that the end of the fish bone could be rediscovered and successfully removed by a video laryngoscope. Finally, with the patient under deep sedation with maintained spontaneous breathing, the fish bone was removed using video laryngoscopy. This case highlights the importance of rechecking CT scans and the use of laryngoscopy when determining the location of a shifted foreign body at different times and when selecting the removal method.